Vitamin D - roles in women's reproductive health? - Grundmann Magdalena (Reproductive Biology and Endocrinology, 2011)
Abstract In the past few years a growing interest in vitamin D can be observed in the lay and biomedical literature due to findings demonstrating a low vitamin D status in the population. In addition to its importance for the regulation of calcium and phosphorus homeostasis recent epidemiologic studies have observed relationships between low vitamin D levels and multiple disease states. This secosteroid hormone also regulates the expression of a large number of genes in reproductive tissues implicating a role for vitamin D in female reproduction. In this report we summarize the recent evidence that vitamin D status influences female reproductive and pregnancy outcomes. Human and animal data suggest that low vitamin D status is associated with impaired fertility, endometriosis and polycystic ovary syndrome. Evidence from observational studies shows higher rates of preeclampsia, preterm birth, bacterial vaginosis and gestational diabetes in women with low vitamin D levels. However, confirmation of experimental observations establishing an association of vitamin D deficiency with adverse reproductive outcomes by high quality observational and large-scale randomized clinical trials is still lacking. The determination of optimal 25(OH)D3 levels in the reproductive period and the amount of vitamin D supplementation required to achieve those levels for the numerous actions of vitamin D throughout a woman's life would have important public health implications.